2013
DOI: 10.1684/ecn.2013.0342
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide distinctly affected TNF-α, IL-6 and MMP secretion by an ovarian cancer cell line (SKOV-3) and primary ovarian cancer cells

Abstract: Background. Thalidomide inhibits TNF-␣ production in lipopolysaccharide-stimulated monocytes. The aim of this study was to evaluate the effect of thalidomide on TNF-␣, IL-6 and MMP secretion in epithelial ovarian carcinoma cells. Materials and methods. SKOV-3 cells and primary epithelial ovarian carcinoma cells were cultured in the presence of various concentrations of thalidomide. Cell proliferation was examined by MTT proliferation assay. TNF-␣ and IL-6 levels were determined in the supernatants of the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Thalidomide was almost inactive, which is in concordance with previous results. [ 18,22 ] Importantly, the growth of nontumor cell line HMEC‐1 was not affected by any treatment. Only compounds 5 and/or 9 minimally inhibited the growth of the tumor cell lines CEM and HeLa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thalidomide was almost inactive, which is in concordance with previous results. [ 18,22 ] Importantly, the growth of nontumor cell line HMEC‐1 was not affected by any treatment. Only compounds 5 and/or 9 minimally inhibited the growth of the tumor cell lines CEM and HeLa.…”
Section: Resultsmentioning
confidence: 99%
“…The experiments were carried out according to the previously published experimental procedure. [ 17,18,22 ] Briefly, the cells were seeded into standard 96‐well microtiter plates and left to attach for 24 hr. The next day, test compounds were added in five serial 10‐fold dilutions.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the anti-inflammatory, anti-angiogenic, and anti-tumor effects of THA may be due to its ability to block the production of TNF-α. 46 THA is thought to inhibit angiogenesis by reducing levels of VEGF as well as TNF-α. Ki 67, a cell nuclear antigen, is associated with cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are reports and studies of thalidomide for the treatment of inflammatory and nociceptive pains as an analgesic or analgesic adjuvant in clinic due to its immunomodulatory and anti-inflammatory properties (Asher and Furnish, 2013;Belda et al, 1966;Chauhan et al, 2012;Ching et al, 2003;Peuckmann et al, 2003;Ribeiro et al, 2000;Schwartzman et al, 2003). Thalidomide can selectively suppress the production of tumor necrosis factor α (TNF-α) (Andrade et al, 2012;Klausner et al, 1996;Marriott, 1997;McHugh and Rowland, 1997;Piura et al, 2013;Schmidt et al, 1996), which plays a pivotal role in the generation of pains. TNF-α can induce the release of interleukin 1b and interleukin 6, which further stimulates the production of cyclo-oxygenase products as well as interleukin 8, a stimulant of the production of sympathomimetic mediators (Marriott, 1997;McHugh and Rowland, 1997;Piura et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thalidomide can selectively suppress the production of tumor necrosis factor α (TNF-α) (Andrade et al, 2012;Klausner et al, 1996;Marriott, 1997;McHugh and Rowland, 1997;Piura et al, 2013;Schmidt et al, 1996), which plays a pivotal role in the generation of pains. TNF-α can induce the release of interleukin 1b and interleukin 6, which further stimulates the production of cyclo-oxygenase products as well as interleukin 8, a stimulant of the production of sympathomimetic mediators (Marriott, 1997;McHugh and Rowland, 1997;Piura et al, 2013). It was reported that thalidomide reduced both mechanical allodynia and thermal hyperalgesia in a mouse chronic constriction injury model of neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%